Millennial Generation's Perception of Larwul Ngabal Customary Law on Dula Island Tual City - Yunus Rahawarin; Pieter Jacob Pelupessy; Rais Rahman Haulusy; Johanis Talaperuw (Multidisciplinary Journal of Thought and Research, 2025)
Indonesia is a plural society (plural society). This pluralism is marked by the diversity of ethnicity, religion, language and culture. Thus giving birth to the order of life and legal norms contained in the form of customary traditions. However, as time has progressed, many millennials do not understand customary law in their local area. In fact, this article discusses how the millennial generation perceives the customary law of Larwul Ngabal in Tual City. This study used a qualitative method, data were collected through direct observation and interviews with five layers of society consisting of the king, traditional leaders, educational leaders, the community and the millennial generation. All results of interviews and field notes were analyzed thematically using the technique analysis interactive assisted Milles & Hubberman model software NVIVO 12.0. The research findings found two perceptions of millennials towards Larwul Ngabal customary law, namely, i) some millennials understand Larwul Ngabal's customary law properly and correctly, they always follow and comply with customary rules; ii) some millennials do not understand Larwul Ngabal's customary law, so they are indifferent and do not follow customary law rules. These two perceptions can be used as a reference for the government, traditional leaders and religious leaders to better introduce and convey to the millennial generation regarding the customary law of Larwul Ngabal on Dula Island, Tual City. So that the millennial generation can understand and implement the customary law of Larwul Ngabal and provide a good perception of this customary law.